KOMUNIKASI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA - Siregar, Nur Fauziah (IAIN PADANGSIDIMPUAN, 2018)
Mathematical communication is one aspect that must be owned and developed in learning mathematics, it is stated in Permen 22 of 2006 concerning Graduation Competency Standards in the field of mathematics. A well-designed mathematics learning process can develop students' mathematical communication skills. The communication process for students to be able to develop ideas and build mathematical knowledge through assignments or questions designed by the teacher. Problems with mathematical communication skills that can be used must be in accordance with mathematical communication indicators. Questions that are in accordance with indicators are questions that can measure students' mathematical abilities. Thus, a good communication process can be a means to teach mathematics. Effective and communicative learning.